The PAediatric Risk Assessment (PARA) Mobile App to Reduce Postdischarge Child Mortality: Design, Usability, and Feasibility for Health Care Workers in Uganda - English, Lauren Lacey; Kumbakumba, Elias; Larson, Charles P.; Barigye, Celestine; Ndamira, Andrew; Kabakyenga, Jerome; Wiens, Matthew O. (JMIR mHealth and uHealth, 2016)
Postdischarge death in children is increasingly being recognized as a major contributor to overall child mortality. The PAediatric Risk Assessment (PARA) app is an mHealth tool developed to aid health care workers in resource-limited settings such as Sub-Saharan Africa to identify pediatric patients at high risk of both in-hospital and postdischarge mortality. The intended users of the PARA app are health care workers (ie, nurses, doctors, and clinical officers) with varying levels of education and technological exposure, making testing of this clinical tool critical to successful implementation.
Keywords: PAediatric Risk Assessment; Postdischarge Child Mortality; Health Care Workers; clinical tool